Pressure tuning of the electrical transport properties in the Weyl semimetal TaP - Besser, M.; Dos Reis, R. D.; Fan, F-R; Ajeesh, M. O.; Sun, Yan; Schmidt, M.; Felser, Claudia; Nicklas, Michael (Physical Review Materials, 2019)
We investigated the pressure evolution of the electrical transport in the almost compensated Weyl semimetal TaP. In addition, we obtained information on the modifications of the Fermi-surface topology with pressure from the analysis of pronounced Shubnikov-de Haas (SdH) quantum oscillations present in the Hall-effect and magnetoresistance data. The simultaneous analysis of the Hall and longitudinal conductivity data in a two-band model revealed an only weak decrease in the electron and hole charge-carrier densities up to 1.2 GPa, while the mobilities are essentially pressure independent along the a direction of the tetragonal crystal structure. Only weak changes in the SdH frequencies for B?a and B?c point at a robust Fermi-surface topology. In contrast to the stability of the Fermi-surface topology and of the density of charge carriers, our results evidence a strong pressure variation of the magnitude of transverse magnetoresistance for B?a contrary to the results for B?c. We can relate the former to an increase in the charge-carrier mobilities along the crystallographic c direction.
CRIS-Team Scopus Importer:2022-04-14